Key Factors for Improving Rigor and Reproducibility: Guidelines, Peer Reviews, and Journal Technical Reviews - Lu, Hong S.; Daugherty, Alan (Frontiers in Cardiovascular Medicine, 2022)
To respond to the NIH’s policy for rigor and reproducibility in preclinical research, many journals have implemented guidelines and checklists to guide authors in improving the rigor and reproducibility of their research. Transparency in developing detailed prospective experimental designs and providing raw data are essential premises of rigor and reproducibility. Standard peer review and journal-specific technical and statistical reviews are critical factors for enhancing rigor and reproducibility. This brief review also shares some experience from Arteriosclerosis, Thrombosis, and Vascular Biology, an American Heart Association journal, that has implemented several mechanisms to enhance rigor and reproducibility for preclinical research.